Methodological recommendations for managing country risks - Veres Somosi, Mariann; Tkachova, N. P. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The report proves that effective risk management of the country requires a systematic approach based on a comprehensive analysis of the external environment and prompt adaptation to changes. In modern conditions, when the international economy faces numerous challenges, taking into account the risks of countries becomes an integral part of strategic management. The implementation of the proposed recommendations contributes not only to minimizing risks, but also to strengthening the positions of companies in international markets.
Методичні рекомендації по управлінню ризиками країн
Keywords: risk; models; minimization; countries; external environment; challenges; strategic management